Analisis Bibliometrik : Model Eliciting Activities Terhadap Kemampuan Koneksi Matematis Berbasis VOSviewer - Juliana, Ika; Rizki, Lussy Midani; Astuti; Zulfah (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Model Eliciting Activities (MEA) is an activity to create or build models and modeling perspectives for mathematical connections in mathematics education. This study aims to determine research trends from generating activities to mathematical connection abilities and to see opportunities for future research based on VOSviewer. This study used bibliometric analysis, the data in this study were obtained through Google Scholar using publish or perish from 2013 to 2023 with the keyword eliciting activities. It was found that the research trend of eliciting activities on mathematical connection abilities in Full Counting Density Visualization contained 54 terms related to mathematical connection abilities. The density display model shows that the most research related to eliciting activities is eliciting open-ended activities, learning outcomes, hots and cognitive styles which are marked in bright yellow. The brighter the yellow color, the more research has been done. While the research that is still small is the ability of mathematical connections, problem solving abilities and critical thinking which are marked with dim colors. Thus, the opportunity to carry out the latest research to retrieve these items can be done because they are rarely studied.